Challenges faced by English language teachers in the implementation of school-based assessment / Hazura Abdul Aziz - Abdul Aziz, Hazura (2013)
The Primary School Standard Curriculum (KSSR) was officially introduced in all national primary schools in Malaysia in 2011. The tides of change have empowered the English Language (EL) teachers in making School-Based Assessment (SBA) decisions in their language teaching and learning process. It is becoming increasingly difficult to ignore the challenges that have washed into the education shore of Malaysia. This study presents the findings of a study on the KSSR SBA implementation challenges faced by the EL teachers in nineteen (19) national primary schools in the Sepang District of Selangor. Data for the study were collected from fifty-three (53) EL teachers using a 53-item survey questionnaire. The findings of this study identified eleven (11) SBA implementation challenges faced by the EL teachers which are divided into two (2) types: Internal Implementation Challenges (IC) and External Implementation Challenges (EC). These challenges are still at a low to moderate level as SBA is in its second year. Three (3) IC are found to be the teachers' professional knowledge, the teachers' professional adequacy and the teachers' professional attitude and motivational interest. The eight (8) EC are school ethos, resource adequacy, in-school professional support, external professional support, ongoing professional development, time, workload, and fairness. The highest ranked SBA IC faced by these EL teachers is the teachers' professional attitude and motivational interest, whereas the highest ranked SBA EC is time. The results of this study indicated that there is a significant difference in the SBA implementation challenges faced by the EL teachers between the 19 national primary schools in the Sepang District of Selangor. When facing the SBA EC, it is found that there is no significant difference between the EL teachers' teaching experience, highest academic qualification and frequentness of attending KSSR SBA in-service training. However, there is a significant difference among the EL teachers' teaching experience when facing the SBA IC in their schools. The study concludes that the teachers' teaching experience is a predictor variable that contributes towards the SBA IC. Five (5) strategies were undertaken by the EL teachers to overcome their SBA implementation challenges: effective time management, creating supportive network of implementation, investing in professional development, communicating a shared vision of intended change and providing continuous assistance. To conclude, the success of the SBA implementation would need the full commitment and support from all education stakeholders in creating a supportive network, investing in professional development, and providing continuous communication to the public and assistance to the teachers. It is recommended for further research that this study should be extended to a wider population from different parties affected by SBA such as the students, parents and school administrative using a variety of data collection instruments.